Snowflake - Weyn, Suzanne; Nang ChanYeema (New York, USA Scholastic Inc., 2006)
While helping out at Fox Creek Farm, three girls try to find a way to pay for a new winter blanket needed by a Percheron horse that is new to the stables.
Keywords: Story Collection